Grillparzers Kunst des Aphorismus - Kaszyński, Stefan H (Studia Germanica Posnaniensia, 2018)
Franz Grillparzer, the classic of Austrian literature wrote, apart from his much valued dramas, short stories and essays, aphorisms which he partly interspersed into his diaries and autobiographical memoirs. The article deals with localization of these aphorisms and their analysis from the point of view of problems they undertake from the point of view of their poetics taking into consideration the theory and history of this genre. It can be seen distinctly from these analyses that Grillparzer was a progenitor and inspirer of later masters of Austrian aphorism from Maria von Ebner-Eschenbach through Karla Kraus to Elias Canetti and Peter Handke.